MANAJEMEN BUDAYA MUTU DI SEKOLAH KEBANGSAAN MALAYSIA (Studi Kasus di Sekolah Kebangsaan Paon Temaga Lundu Malaysia) - yarso, Hasminuddin; Syukri, M.; Sukmawati, Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of the research was to obtain deep information on the strategy of quality culture management in Paon Temaga National School Malaysia and got Excellent Cluster predicate in the border area of Indonesia - Malaysia. This research used descriptive method and qualitative approach with a case study design. The data sources were the headmaster, teachers, the chair of parents-teacher association (PIBG), and parents. The data were collected through deep interview, non participant observation, and document study. The data analysis was done through three phases namely data reduction, data validation, and data verification. The grand theory used as the basis for this research were theory of Yoseph Juran, Deming (1982), Crosby and Ishikawa, theory of organizational climate and culture by Gamage & Pang (2003), theory of total quality management by Sallis (2012), and also supported by theory ofÂ  developing visionary leadership by Hidayah N (2014), theory of school parenting in elementary school or school-based involvement (Hill & Taylor, 2004) and brain-based learning (i-Think) by Erick Jensen (2008). Based on the analysis, it can be concluded that quality culture management in Paon Temaga National School Malaysia started from developing School Parenting and i-Think as the leading program until they get the predicate of excellent cluster school at national rank. Implementation of school parenting and i-Think with high discipline and spirit of teamwork has brought a significant change on the effectiveness of school quality culture. Â Keywords: School Parenting, I-Think, Quality Culture